2018
DOI: 10.1093/jpepsy/jsy071
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Emotional Control Moderates Benefits of a Multicomponent Intervention to Improve Type 1 Diabetes Adherence: A Pilot Randomized Controlled Trial

Abstract: This multicomponent, web-delivered intervention provided unique benefits for improving SMBG and lowering HbA1c in teens with higher problems in emotional control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Of note, some seemingly disorderspecific mechanisms may be in fact transdiagnostic but are as yet untested (e.g., shame) or tested against a different measurement of adversity. From a lifespan perspective, the current findings are consistent with similar research in early adversity and psychopathology in adolescence, where the mediating role of processes identified in the current review, including emotion regulation, social support, cognitive appraisals and self-concept, has also been identified (Dhondt et al, 2019;John et al, 2017;Lansing et al, 2019;Negriff et al, 2019;Paredes & Calvete, 2014).…”
Section: Summary Of Findingssupporting
confidence: 88%
“…Of note, some seemingly disorderspecific mechanisms may be in fact transdiagnostic but are as yet untested (e.g., shame) or tested against a different measurement of adversity. From a lifespan perspective, the current findings are consistent with similar research in early adversity and psychopathology in adolescence, where the mediating role of processes identified in the current review, including emotion regulation, social support, cognitive appraisals and self-concept, has also been identified (Dhondt et al, 2019;John et al, 2017;Lansing et al, 2019;Negriff et al, 2019;Paredes & Calvete, 2014).…”
Section: Summary Of Findingssupporting
confidence: 88%
“…255 Also more complex interventions, such as an multicomponent motivational and cognitive intervention targeting youth with suboptimal glycemic management and emotional regulation difficulties, can be delivered via the Internet as it resulted in increased frequency of blood glucose monitoring, improved working memory, and improved glycemic management 256 ; youth with more emotional control problems benefited the most from this approach. 257 Digital health interventions (i.e., programs or tools which use digital technology to encourage or foster behavior change, such as websites, mobile applications [apps], text messaging, or online games) for youth with diabetes have some impact on their mental health such as self-efficacy, but few consistent effects for other psychological, behavioral, or health outcomes; results also indicated studies showed high risk of bias and more research was needed using theory-based approaches with stronger methodologies. 258…”
Section: Internet-based and Digital Interventionsmentioning
confidence: 99%
“…Further, adolescents respond well to behavioral intervention using Skype, 228 tele‐health, 253 text messaging, 227,254 and can receive social support via chat rooms 255 . Also more complex interventions, such as an multicomponent motivational and cognitive intervention targeting youth with suboptimal glycemic management and emotional regulation difficulties, can be delivered via the Internet as it resulted in increased frequency of blood glucose monitoring, improved working memory, and improved glycemic management 256 ; youth with more emotional control problems benefited the most from this approach 257 …”
Section: Psychosocial and Behavioral Interventionsmentioning
confidence: 99%
“…Behavioral treatment modalities such as working memory training have been used in adolescents with type 1 diabetes and show some benefits, especially when combined with other psychological treatments. 32…”
Section: Eating Disordersmentioning
confidence: 99%